2017
DOI: 10.1111/micc.12350
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic blockade does not impair the skin blood flow sensitivity to local heating in burned and nonburned skin under neutral and hot environments in children

Abstract: Objective Tested the hypothesis that propranolol, a drug given to burn patients to reduce hypermetabolism/cardiac stress, may inhibit heat dissipation by changing the sensitivity of skin blood flow (SkBF) to local heating under neutral and hot conditions. Methods In a randomized double-blind study, a placebo was given to 8 burned children while propranolol was given to 13 burned children with similar characteristics (mean ± SD: 11.9±3y, 147±20cm, 45±23kg, 56±12% TBSA). Non-burned children (n=13, 11.4±3y, 152… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…These children report crying, nausea, and fatigue. Notably, we have previously shown that burned children have profound elevations in skin blood flow perfusion (40-60% of max) compared to non-burned controls (∼10% of max)(30). Because of the hyper metabolic state and inability of damaged skin to regulate body temperature, issues that are similar to those seen in patients with heart failure may contribute to an impaired cardiovascular response to exercise due to the profound redistribution of blood to the peripheral skin; however, this is speculative and requires further understanding.…”
Section: Discussionmentioning
confidence: 99%
“…These children report crying, nausea, and fatigue. Notably, we have previously shown that burned children have profound elevations in skin blood flow perfusion (40-60% of max) compared to non-burned controls (∼10% of max)(30). Because of the hyper metabolic state and inability of damaged skin to regulate body temperature, issues that are similar to those seen in patients with heart failure may contribute to an impaired cardiovascular response to exercise due to the profound redistribution of blood to the peripheral skin; however, this is speculative and requires further understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in healthy adults, the administration of propranolol during exercise under heat stress was found to decrease sweating [134]. Rivas et al [135] carried out a study to evaluate the putative reduction in heat dissipation, mediated by propranolol, in burned patients, whose thermal homeostasis is disrupted due to the inability of burned skin to control heat loss. However, these researchers found that therapeutic propranolol does not negatively affect skin blood flow and further compromises temperature regulation in burned children.…”
Section: Cardiovascular System Drugs That May Affect Hydration Statusmentioning
confidence: 99%
“…We have previously reported that the cardiovascular response to submaximal exercise is diminished in burned children compared with nonburned age-or sex-matched children. 27,28 Thus, burn trauma may have a more pronounced effect in children than adults, and this requires further understanding. Notably, adults have important body morphology characteristics that differ from those of children in early stages of development.…”
Section: Discussionmentioning
confidence: 99%
“…30 Most importantly, Reynolds et al found that, in children, burn injury causes cardiac failure, particularly left ventricular myocardial depression, and that this outcome that was likewise different from that seen in burned adults. 31 We have recently reported that, during submaximal exercise, burned children have exercise intolerance and attenuated peak heart rate values compared with nonburned age-or sex-matched children 27,28 ; however, this type of investigation has not been conducted in burned adults to date. Relative submaximal heart rate (row A) and peak oxygen uptake (row B) during the first three stages of the modified Bruce exercise in men and boys at discharge (pre-training) and after rehabilitation training (post-training) in men and boys.…”
Section: Discussionmentioning
confidence: 99%